The International Encyclopedia of Media Psychology 2020
DOI: 10.1002/9781119011071.iemp0175
|View full text |Cite
|
Sign up to set email alerts
|

Affective Disposition Theory and Disposition Theory

Abstract: Affective disposition theory (ADT) explains how and why audience members enjoy entertainment narratives. More specifically, ADT describes (i) how viewers form affective dispositions toward media characters, (ii) how doing so triggers anticipatory emotional reactions to the unfolding events involving those characters, and (iii) how those emotional responses and the outcomes portrayed result in enjoyment. ADT contends that enjoyment increases the more characters experiencing positive outcomes are liked and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…One factor has recently emerged as a possible explanation: identification. In fact, a few ADT-informed studies (Janicke & Raney, 2015; Raney et al, 2009; Tsay & Krakowiak, 2011) have tentatively shown that identification is an important variable through which dispositions are formed toward the antihero.…”
Section: Affective Disposition Theory and Antihero Enjoymentmentioning
confidence: 99%
See 4 more Smart Citations
“…One factor has recently emerged as a possible explanation: identification. In fact, a few ADT-informed studies (Janicke & Raney, 2015; Raney et al, 2009; Tsay & Krakowiak, 2011) have tentatively shown that identification is an important variable through which dispositions are formed toward the antihero.…”
Section: Affective Disposition Theory and Antihero Enjoymentmentioning
confidence: 99%
“…In fact, preliminary research suggests that, among fans, enjoyment of an episode of the TV series 24 increased the more that fans judged the lead character Jack Bauer to be unattractive and immoral (Janicke & Raney, 2015). One prominent explanation (Krakowiak & Tsay, 2011; Raney et al, 2009; Tsay & Krakowiak, 2011) is that viewers actually recast the immoral behavior as moral—or at least, as justified—through the process of moral disengagement (Bandura, 1999).…”
Section: Moral Disengagementmentioning
confidence: 99%
See 3 more Smart Citations